Production of Protease Enzymes and Bioactive Compounds by Lactic Acid Bacteria (LAB) From Broccoli (Brassica oleracea L.) Using Lactobacillus plantarum Starter - Hidayat, Habibi; Maharani, Najlaa Ayu; Maulani, Qisti; Fajarwati, Febi Indah (EKSAKTA: Journal of Sciences and Data Analysis, 2026)
This study aimed to isolate and characterize Lactic Acid Bacteria (LAB) from broccoli (Brassica oleracea L.) with potential protease-producing activity and probiotic properties. Fermentation was carried out using Lactobacillus plantarum as a starter culture. The obtained LAB isolates were subsequently evaluated for protease activity and analyzed for bioactive compound content. The results demonstrated that LAB isolates obtained from broccoli were capable of producing proteases with significant activity, indicating their potential for biotechnological applications. In addition, the isolates produced bioactive compounds exhibiting antibacterial activity against several pathogenic bacteria, including S. epidermidis, K. pneumoniae, E. coli, S. aureus, S. typhi, and S. pyogenes, as evidenced by the formation of inhibition zones. The isolate demonstrated strong antibacterial activity against all tested pathogens with inhibition zones of 56 mm for S. epidermidis, 30 mm for S. typhi, 12 mm for both K. pneumoniae and E. coli, and 11 mm for S. pyogenes and S. aureus. Acid tolerance assays demonstrated that the LAB isolates survived at low pH, and protease activity assays showed that the isolate produced an enzyme with proteolytic activity of 23.5 mm and 0.0440 U/mL.